Primary Care-Led Transition Clinics Hold Promise in Improving Care Transitions for Cancer Patients Facing Social Disparities: A Commentary. (September 2020) - Malebranche, Mary; Sarivalasis, Apostolos; Peters, Solange; Mathevet, Patrice; Cornuz, Jacques; Bodenmann, Patrick
Transitions in care are key junctions during which care coordination, communication, and individualized support are required to ensure optimal health outcomes for patients. This is particularly true for patients who face social disparities, such as poverty, limited health literacy, or belonging to a racial or ethnic minority, who are particularly at risk for experiencing poor care transitions. Interdisciplinary primary care-led transition clinics are an intervention that have shown promise in improving care transitions for diverse patient populations, including those that face social disparities, but their role in improving transitions in cancer care remains largely untapped. In this commentary we highlight why the time-limited support of an interdisciplinary primary care-led transition clinic that targets socially vulnerable cancer patients holds the promise of achieving more equitable healthcare access, healthcare quality, and ultimately more equitable health outcomes for cancer patients.